2013
DOI: 10.2146/ajhp130171
|View full text |Cite
|
Sign up to set email alerts
|

Management of digoxin therapy using pharmacokinetics in a patient undergoing continuous venovenous hemofiltration

Abstract: Analysis of serum digoxin concentration and digoxin Cuf values suggested that digoxin was cleared by CVVH, allowed calculation of Sc and CLtm values, and facilitated determination of digoxin requirements in a critically ill patient requiring CVVH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The majority (50-70%) of digoxin is renally eliminated, unchanged in a linear fashion, highlighting the importance of dose adjustment in renal dysfunction [21,22]. Guidance regarding dosage adjustments in iHD and CRRT are scarce, with current recommendations suggesting to administer 50% of the loading dose followed by administering 62.5mcg every 48 hours for iHD or 62.5 mcg -125 mcg every 48 hours for CRRT [4,7]. Monitoring digoxin in patients that are on chronic digoxin is important as it has a narrow therapeutic index, with a goal of serum level of 0.8-1.2 ng/mL for A b and 0.5-0.7 ng/ml for heart failure [23,24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority (50-70%) of digoxin is renally eliminated, unchanged in a linear fashion, highlighting the importance of dose adjustment in renal dysfunction [21,22]. Guidance regarding dosage adjustments in iHD and CRRT are scarce, with current recommendations suggesting to administer 50% of the loading dose followed by administering 62.5mcg every 48 hours for iHD or 62.5 mcg -125 mcg every 48 hours for CRRT [4,7]. Monitoring digoxin in patients that are on chronic digoxin is important as it has a narrow therapeutic index, with a goal of serum level of 0.8-1.2 ng/mL for A b and 0.5-0.7 ng/ml for heart failure [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…A case report by Benken et al sought to investigate the effects of continuous venovenous hemo ltration (CVVH) on digoxin clearance [4]. The researchers calculated the sieving coe cient and transmembrane clearance for digoxin to be 0.8 and 30 mls/min, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kaneko et al showed successful treatment of digoxin toxicity with hemoperfusion using a specific column for β2‐microglobulin‐adsorption in a hemodialysis patient but the availability of the column and lack of trials are the main concerns about this modality 7 . Benken et al investigated the pharmacokinetics of digoxin and showed a decrease in serum digoxin concentrations with continuous venovenous hemofiltration in a heart failure patient without any drug toxicity 8 . We report, for the first time in the literature, a case of acute severe digoxin toxicity with severe acute kidney injury who was successfully treated with CVVHD treatment.…”
Section: Discussionmentioning
confidence: 99%
“…7 Benken et al investigated the pharmacokinetics of digoxin and showed a decrease in serum digoxin concentrations with continuous venovenous hemofiltration in a heart failure patient without any drug toxicity. 8 We report, for the first time in the literature, a case of acute severe digoxin toxicity with severe acute kidney injury who was successfully treated with CVVHD treatment.…”
Section: Continuous Hemodialysis In Digoxin Toxicitymentioning
confidence: 97%